ETHICAL IMPLICATIONS OF HUMAN RESOURCE DEVELOPMENT ANDAPPLICATION OF ARTIFICIAL GENERAL INTELLIGENCE (AGI) IN THE CONTEXT OF GLOBAL BUSINESS GOVERNANCE - Lince Bulutoding; Nur Rahmah Sari; Rasty Yulia; Vinno P. Manoppo; Al-Amin (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2023)
This research delved into the ethical ramifications of integrating Artificial General Intelligence (AGI) into Human Resource Development (HRD) within the framework of global business governance. The study addressed the increasing adoption of AGI technologies in HRD practices across diverse international organizations. It explored the potential benefits of AGI in streamlining HRD processes, enhancing efficiency, and providing data-driven insights. However, the research also highlighted the ethical dilemmas accompanying this technological transformation. Issues such as algorithmic bias, invasion of employee privacy, and the responsibility of organizations to ensure fairness and inclusivity emerged as central concerns. The study highlighted the critical importance of addressing these ethical challenges to maintain the integrity of HRD practices. In the context of global business governance, the research emphasized the need for organizations to navigate a complex web of regulations, industry standards, and cultural nuances. Compliance with global governance mechanisms was recognized as essential to align AGI-driven HRD with ethical principles on an international scale. The findings underscored the significance of responsible AGI deployment and collaboration with global governance frameworks to uphold human rights and data privacy. The study concluded by calling for a proactive approach to AGI ethics, ensuring that the transformative potential of AGI in HRD is harnessed while safeguarding the well-being and rights of employees worldwide.